2016
DOI: 10.1080/10253890.2016.1203414
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces catecholamine production in mesenteric adipose tissue of rats previously exposed to immobilization stress

Abstract: Catecholamines (CAs) are mainly produced by sympathoadrenal system but their de novo production has been also observed in adipose tissue cells. The aim of this work was to investigate whether immune challenge induced by lipopolysaccharide (LPS) modulates biosynthesis of CAs in mesenteric adipose tissue (MWAT), as well as whether previous exposure to immobilization (IMO) stress could modulate this process. Sprague-Dawley rats were exposed to single (2 h) or repeated (2 h/7 days) IMO and afterwards injected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Recent studies have suggested that the M1-M2 switch in adipose tissues is caused by diff erential recruitment of various monocyte subtypes (Lumeng et al 2008). Since we have previously found correlation between F4/80 and TH expression in the mWAT, rising number of M2 macrophages may participate in CA production (Vargovic et al 2016). Elevated monocyte infi ltration in WAT is observed especially in obesity but with dominant M1 phenotype associated with infl ammation, resistin expression, and pathological consequences related to insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that the M1-M2 switch in adipose tissues is caused by diff erential recruitment of various monocyte subtypes (Lumeng et al 2008). Since we have previously found correlation between F4/80 and TH expression in the mWAT, rising number of M2 macrophages may participate in CA production (Vargovic et al 2016). Elevated monocyte infi ltration in WAT is observed especially in obesity but with dominant M1 phenotype associated with infl ammation, resistin expression, and pathological consequences related to insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We have identifi ed CA biosynthetic enzymes expression in the brown and white adipose tissues and described the stimulation of CA production in the cell fractions of the mesenteric adipose tissue in response to immobilization or cold stress (Vargovic et al 2011;Kvetnansky et al 2012;Vargovic et al 2013;Vargovic et al 2016). Since only the mWAT showed stress-inducible cell-specifi c CA production, from all the investigated adipose tissues (brown, epididymal, retroperitoneal, subcutaneous), we suppose that the mWAT may represent another active site of the beige adipogenesis, similarly as it has been described in the case of the scWAT.…”
mentioning
confidence: 99%
“…The upregulation of TH in adipocytes and preadipocytes by IFNγ and IL-4 stimulation may reflect an increase of CA synthesis to counteract the inflammatory environment. Notably, IL-4 was also reported to increase TH expression in macrophages [10]. There was no observable difference in the expression pattern of TH, PNMT and PPARγ in preadipocytes and adipocytes after pro (INF-γ) or anti-inflammatory (IL-4) cytokines exposure.…”
Section: Discussionmentioning
confidence: 85%
“…The interplay between adipokines and CA [9] suggests a role for these molecules linking obesity to inflammation. Indeed, in rat visceral AT lipopolysaccharides (LPS) and immobilization insults modulate the immune response and increase macrophage infiltration associated with endogenous CA production [10]. CA signaling in macrophages has been reported to modulate inflammation by decreasing TNF-α secretion [14].…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation